Morphometric parameter of valleys east of Wasit government using the Geographical Information Systems - Abood, Abdullah Sabbar; Abbass, Hamza Jassim (Al-Adab Journal, 2021)
The purpose of this research is to reveal the morphometric characteristics of the basins of the Tarsagh valleys, Kalal Badra, Al-Ziyadi and Wadi Al-Shehabi basin, using geographic information systems and methods of quantitative analysis of the various surface phenomena in the region. The study of the morphometric characteristics showed that the shape of the basins approached elongation and moved away from the roundness, which means slowing down the arrival of water waves to the exits of the basins, and then increasing the volume of water losses by leakage and evaporation, which makes the indication of the risk of flooding relatively small for these basins.